Literasi Keuangan dan Efikasi Keuangan terhadap Minat Investasi Emas Antam Masyarakat Desa Labanjaya Kecamatana Pedes Kabupaten Karawang - Hidayat, Ahmad Wahyu; Sihabudin, Sihabudin; Fauji, Robby (BUDGETING : Journal of Business, Management and Accounting, 2024)
The aim of this research is to explain Financial Literacy and Financial Efficacy of the Antam Gold Investment Interest of the Labanjaya Village Community. This research uses Descriptive Verification. The sample in this research was determined using the Lemeshow formula of 96 community respondents. Data was obtained using a Likert scale questionnaire distributed using Google Form. The data analysis method uses Multiple Linear Regression Analysis using SPSS version 26 tools. The results of this research show that the Financial Literacy Variable has a positive and significant effect on Investment Interest, and the Financial Efficacy Variable has a significant positive effect on Investment Interest, and Financial Literacy and Financial Efficacy have a positive effect and significant to Investment Interest. Keywords: Financial Efficacy, Financial Literacy, Investment Interest.